Tindakan Menaiki Kapal Asing Yang Melintasi Pelayaran Internasional Oleh Militer Negara Lain - Siwabessy, Elsa Jhon; Peilouw, Johanis Steny Franco; Leatemia, Wilshen (PATTIMURA Law Study Review, 2025)
The concept of "Res communis" which states that the sea belongs to the common property of all people of the world. In a video released by the Iranian Navy, a group of soldiers of the Islamic Revolutionary Guard Corps (IRGC) plunge aboard the Advantage Sweet oil tanker bound for Houston in the Gulf of Oman on Thursday, April 27. This type of research is normative juridical where research is carried out by collecting primary, secondary and tertiary data obtained using literature studies. The collected legal materials are analyzed qualitatively, the elaboration of which is systematically arranged based on legal disciplines. Based on the results of the research, freedom on the high seas is regulated in the United Nations Convention on the Law of the Sea (UNCLOS 1982) which is the basis of international law on the high seas that gives the right to freedom of navigation to all ships. This includes the right to sail, fly, and perform other maritime activities without hindrance. Regulations on the high seas are regulated by UNCLOS 1982 in Article 87 concerning freedom on the high seas, namely, freedom of navigation, freedom of flight, freedom to install submarine cables and pipelines, freedom to build artificial islands, freedom to fish and freedom of scientific research. in the act of Iran boarding the Adventage Sweet, on the international shipping channel. cannot be justified because this is a direct violation of the provisions of the 1982 Convention, one of which is freedom of navigation in international seas. This action is a violation because the ship is not proven to have committed a violation.